PENGARUH STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMEN PADA RESORT CAFÉ ATMOSPHERE BANDUNG - resti meldarianda; Henky Lisan S (Jurnal Bisnis dan Ekonomi, 2010)
Rapid economic growth in Indonesia creates tight competition in business,including culinarybusiness. This make businessman have to work hard to maintain old customers and attract newcustomers at the same time. One of many ways can be used to gain consumer’s purchase intentionis to create and to improve instore atmosphere and outstore atmosphere, commonly known asstore atmosphere. The aim of this research is to know the influence of store atmosphere towardsconsumer’s purchase intention in Atmosphere Resort Café Bandung. The research method used bywriter is non probability sampling by spearing questioners to 125 respondents, who areBandung’s residents ever visited Atmosphere Resort Café Bandung.Collected data then managedand analyzed using statistic test. Base on managed and processed data, it is acknowledge that sig.= 0,000 < 0,05, so rejected Ho means there are influences between store atmosphere andcustomers purchase intention in Atmosphere Resort Café Bandung, which is around 14,6%, while85,6% influenced by other factors excluded in this research. From the result, the writer try tosuggest in choosing atmosphere or theme as store atmosphere has to be well-concepted,consistent, unique, and original.Keywords: atmosphere, store atmosphere, instore atmosphere, outstore atmosphere, purchase intention.